Preposition Stranding and que-deletion in Varieties of North American French. - Roberge, Yves; Rosen, Nicole (Linguistica Atlantica, 1999)
Comparative studies of the differences between North-American varieties of French (NAF) and Standard French (SF) reveal that most variation is found in the lexical and phonological systems. This type of variation is well-documented. However, this is not the case for the syntactic component, which could lead one to believe that there are very few syntactic differences between NAF and SF. This article deals with some differences between NAF and SF in the prepositional and complementizer systems. More precisely, we argue that the fact that stranded prepositions appear more freely in NAF than in SF is related to facts regarding variation in the complementizer system.